Dampak Strategi Bauran Pemasaran Dan Kualitas Pelayanan Terhadap Tingkat Partisipasi Anggota Sebagai Pengguna Koperasi - TIRIS SUDRARTONO (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2018)
This study aims to find out how big the impact of Marketing Mix Strategy and Service Quality to Member Participation Level As a cooperative user, the sample in this research is 97 members of cooperative work of prosperous PT.Polyfin Canggih as respondents who answered the statement of the questionnaire distributed then analyzed quantitatively and qualitatively. Data from equation test is known F-count value is 114,782 while with -table value 3,94. This means that F-stat> F-table (114,782> 3,94) means that at 95% confidence level, Marketing Strategy and Service Quality variables have a significant influence simultaneously on the variable Member participation rate as a Cooperative User. The coefficient of determination (R2) is 0.709. Member Participation Rate of 70.9% is influenced by the Marketing Mix Strategy and Service Quality and the balance of 29.1% is influenced by other factors outside the model.